DESAIN ONLINE LEARNING PADA KURSUS DESAIN GRAFIS DI LKP VISION COLLEGE SEMARANG - An Nissa Hafna Muthi'ah; Yudi Siswanto (STKIP Pesisir Selatan, 2026)
Digital technology development has driven learning transformation in course and training institutions, particularly in practical skills fields such as graphic design. This study aims to identify online learning design in graphic design courses using the ICCEE model at LKP Vision College Semarang. Employing a descriptive qualitative approach with purposive sampling, this research selected informants who understand the research context, including instructors directly involved in online learning design and implementation, institutional administrators establishing course policies and strategies, and online graphic design course participants. Data were collected through in-depth interviews exploring the identify, choose, create, engage, and evaluate processes; non-active participatory observation documenting learning interactions and strategies; and documentation studies of syllabi, modules, teaching materials, and evaluation instruments. Data validity was ensured through source and method triangulation. Findings reveal that online learning design in graphic design courses at LKP Vision College Semarang follows a systematic framework aligned with the ADDIE model and oriented toward Competency-Based Training. This research expands understanding of online learning design in practice-based non-formal education, demonstrating that online learning success depends not only on technology but also on systematic instructional design, instructor support, and institutional policies adaptive to creative industry needs.